Hubungan Penggunaan Media LCD (Liquid Crystal Display) Proyektor Terhadap Hasil Belajar Matematika Siswa Kelas V SDN Sungkai 1 Kabupaten Banjar - Astuti, Nadya (Indo-MathEdu Intellectuals Journal, 2023)
This study aims to determine the effect of using LCD projectors on Mathematics learning outcomes in grade V students of SDN Sungkai 1 Banjar Regency. The population in this study was all grade V students of SDN Sungkai 1 Banjar Regency with a total of 56 students. The research method used in this study is quasi experiments with non-equivalent control group design. Data collection techniques are observation and tests. Data analysis techniques use quantitative data analysis, namely correlation analysis. When viewed from the average posttest value and calculation using the N-Gain formula with results of 0.22 where 0.22 ≤ 0.30 in the low category for the control class and 0.52 where 0.30 ≤ 0.52 ≤ 0.70 with the medium category for the experimental class, it can be concluded that there is an influence of the use of LCD (Liquid Crystal Display) projector media on the mathematics learning outcomes of grade V students of SDN Sungkai 1 Banjar Regency. Teachers should be able to use LCD projectors in learning to increase students' interest in learning